RESEARCH ON LEARNING PROBLEMS IN YOUNG ENGLISH LEARNERS THROUGH MOBILE AND ANIMATED FILMS - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
Our article is devoted to studying the influence of animated films and mobile applications on the process of learning English among young students and the results of their implementation in the educational system.